Screening for Congenital Hypothyroidism in Newborns Transferred to Neonatal Intensive Care - Korzeniewski, Steven J. (2012)
OBJECTIVE: To evaluate the effectiveness of four screening protocols for congenital hypothyroidism (CH) in newborns transferred to the NICU. Determine an evidence base for the Center for Laboratory Standards Institute’s Newborn Screening for Preterm, Low Birth Weight, and Sick Newborns Approved Guideline by evaluating a nearly identical protocol. DESIGN, SETTING & PATIENTS: Michigan newborns transferred to the NICU from 1998–2011 and screened for CH are included in this population-based retrospective cohort study. MAIN OUTCOME MEASURES: Screening performance metrics are computed and logistic regression is used to test for differences in the likelihood of detection across four periods characterized by different testing protocols. RESULTS: Primary TSH plus retest at 30 days of life or discharge achieved the greatest detection rate (2.6: 1,000 births screened). The odds of detection was also significantly greater in this period compared to the tandem T4 and TSH testing period and separately compared to TSH testing alone, adjusted for birth weight, sex and race (aOR 1.5; CI 1.0–2.2; p=0.046, and aOR 2.2; CI 1.5–3.4, respectively). Approximately half of the cases detected during primary TSH plus serial testing periods were identified by retest. CONCLUSION: Primary TSH testing programs that do not incorporate serial screening may fail to identify approximately half of newborns with congenital thyroid hormone deficiency transferred to the NICU. Tandem T4 and TSH testing programs also likely miss cases who otherwise would receive treatment if serial testing were conducted. Further research is necessary to determine the optimal NBS protocol for CH; strategies combining tandem T4 and TSH with serial testing conditional on birthweight may be useful.